Carbon nanotube-composite hydrogels promote intercalated disc assembly in engineered cardiac tissues through β1-integrin mediated FAK and RhoA pathway. (15th January 2017) - Sun, Hongyu; Tang, Jiajia; Mou, Yongchao; Zhou, Jing; Qu, Linlin; Duval, Kayla; Huang, Zhu; Lin, Ning; Dai, Ruiwu; Liang, Chengxiao; Chen, Zi; Tang, Lijun; et al.
Graphical abstract: Abstract: Carbon nanotube (CNT)-based hydrogels have been shown to support cardiomyocyte growth and function. However, their role in cellular integrity among cardiomyocytes has not been studied in detail and the mechanisms underlying this process remain unclear. Here, single walled CNTs incorporated into gelatin with methacrylate anhydride (CNT/GelMA) hydrogels were utilized to construct cardiac tissues, which enhanced cardiomyocyte adhesion and maturation. Furthermore, through the use of immunohistochemical staining, transmission electron microscopy and intracellular calcium transient measurement, the incorporation of CNTs into the scaffolds was observed to markedly enhance the assembly and formation in the cardiac constructs. Importantly, we further explored the underlying mechanism behind these effects through the use of immunohistochemical staining and western blotting. The β1-integrin-mediated FAK and RhoA signaling pathways were found to be responsible for CNT-induced upregulation of electrical and mechanical junction proteins respectively. Together, our study provides new insights into the facilitative effects of CNTs on ID formation, which has important significance for improving the quality of engineered cardiac tissue and applying them to cardiac regenerative therapies. Statement of Significance: Currently, the bottleneck to engineering cardiac tissues (ECTs) for cardiac regeneration is the lack of efficient cellular integrity among adjacent cells, especially the insufficient remodeling of intercalated discs (IDs) in ECTs. Recently, carbon nanotube (CNT) hydrogels provide an advantageous supporting microenvironment and therefore benefit greatly the functional performance of ECTs. Although their beneficial effect in modulating ECT performance is evident, the influence of CNTs on structural integrity of ECTs has not been studied in detail, and the mechanisms underlying the process remain to be determined. Here, we utilized carbon nanotube incorporated into gelatin with methacrylate anhydride (CNT/GelMA) hydrogels to construct cardiac tissues, determined the influence of CNTs on intercalated discs (IDs) assembly and formation and explored the underlying mechanisms.